The Protective Role of Friendship: Crossgroup Friendship Mediates the Effect of Ideological Quest for Significance on Commitment to A Radical Group - Milla, Mirra Noor; Hudiyana, Joevarian (Psychological Research on Urban Society, 2019)
On the basis of the Quest for Significance theory, a person’s sense of meaning and personal significance may be obtained from ideological narratives. The more a radical ideology gives a person a sense of meaning, the less likely it is that he or she will engage in interpersonal relations and friendships with out-group members. In this study, we hypothesized that ideological quest for significance would predict commitment to a radical group and that this association would be mediated through cross-group friendship. This research was based on interviews with 241 prisoners at 59 Indonesian prisons, who were serving sentences for terrorism offenses. Mediation analysis found that higher scores on ideological quest for significance significantly predicted lower scores on cross-group friendship, and lower scores on cross-group friendship significantly predicted higher scores on commitment to a radical group. There was a significant direct effect of ideological quest for significance on commitment to a radical group and a significant indirect effect using the bootstrapping method. This suggested that the effect of ideological quest for significance on commitment to a radical group was partially mediated by cross-group friendship.